Which Head and Neck Cancer Patients Are Most at Risk of High Levels of Fear of Cancer Recurrence - Rogers, Simon N.; Monssen, Camilla; Humphris, Gerald M.; Lowe, Derek; Kanatas, Anastasios (Frontiers in Psychology, 2021)
Background: Fear of cancer recurrence (FCR) is recognised as a common concern for patients with head and neck cancer (HNC). The aim of this study is to describe in greater detail the demographic and clinical characteristics of HCN patients who indicate a high level of FCR in their review consultation. Methods: A pragmatic cluster-controlled trial was conducted between January 2017 and December 2018 at two UK HNC centres (Leeds and Liverpool) to test the efficacy of a prompt tool called the Patient Concerns Inventory (PCI). Patients completed the PCI and the UW-QOLv4 which included a single 5 category rating of FCR. Secondary statistical analyses focussed on variables associated with high FCR. Results: 288 trial patients were recruited in this trial. At a median of 194 days after diagnosis and 103 days after the end of treatment 8% stated (n=24) “I get a lot of fears of recurrence and these can really preoccupy my thoughts” and 3% (n=8) “I am fearful all the time that my cancer might return, and I struggle with this”. Thus 11% (n=32) responded in the worst two categories, 95% Confidence interval 7.7-15.3% for high FCR. Stepwise logistic regression resulted in female gender (p<0.001), age (p=0.007) and receiving financial benefits (p=0.01) as independent predictors. Conclusions: Around one in ten HNC patients attending routine outpatient follow-up consultations report high FCR, however for female patients under the age of 55 the rate was one in three. This group requires specialist attention and could be the focus of a multicentre intervention trial.